The Effect of Parental Attention on Learning Outcomes of High School Students - Dwinanda, Furmanissa Okta; Mediatati, Nani (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to determine whether parental attention significantly influences students' learning outcomes in class XI IPS 1 SMA Negeri 1 Wonosegoro in Civics subjects. This research uses a quantitative approach and uses explanatory research. Primary data comes from questionnaires, while secondary data comes from school data and books. The population in this study were all students of class XI SMA Negeri 1 Wonosegoro totaling 216 students. Sampling in this study was determined non-randomly, namely students of class XI IPS 1 with a total of 36 students. Data collection techniques used questionnaires or questionnaires, documentation, and interviews. Data collection techniques used questionnaires and learning outcomes documents. Furthermore, the data analysis technique uses simple linear regression test statistics with the SPSS version 20 program. Based on the results of the simple linear regression test, it can be concluded that HO is accepted and HI is rejected, meaning that there is no significant effect of parental attention on the learning outcomes of students in class XI IPS 1. The R Squares value is 0.071, which shows that the effective contribution of parental attention variables in influencing learning outcomes is 7.1%. The rest is influenced by other variables that are not studied.